The Laboratory Diagnosis of Neisseria gonorrhoeae: Current Testing and Future Demands - Thomas Meyer; Susanne Buder (Pathogens, 2020)
The ideal laboratory test to detect Neisseria gonorrhoeae (Ng) should be sensitive, specific, easy to use, rapid, and affordable and should provide information about susceptibility to antimicrobial drugs. Currently, such a test is not available and presumably will not be in the near future. Thus, diagnosis of gonococcal infections presently includes application of different techniques to address these requirements. Microscopy may produce rapid results but lacks sensitivity in many cases (except symptomatic urogenital infections in males). Highest sensitivity to detect Ng was shown for nucleic acid amplification technologies (NAATs), which, however, are less specific than culture. In addition, comprehensive analysis of antibiotic resistance is accomplished only by in vitro antimicrobial susceptibility testing of cultured isolates. As a light at the end of the tunnel, new developments of molecular techniques and microfluidic systems represent promising opportunities to design point-of-care tests for rapid detection of Ng with high sensitivity and specificity, and there is reason to hope that such tests may also provide antimicrobial resistance data in the future.